Co-gasification of coal/sewage sludge blends to hydrogen-rich gas with the application of simulated high temperature reactor excess heat. (25th May 2016) - Smoliński, Adam; Howaniec, Natalia
Abstract: The experimental study on oxygen and steam gasification and co-gasification of hard coal and sewage sludge to hydrogen-rich gas was performed in the laboratory scale fixed bed gasifier equipped with an auxiliary gasification agents pre-heating system, simulating the utilization of an excess High Temperature Reactor (HTR) heat. The allothermal gasification and co-gasification tests were performed on fuel blends of coal and sewage sludge of the total mass of 10 g and biowaste content of 20% and 40%w/w in three system configurations. In the first one the reactor was heated up with a resistance furnace to the temperature of 700 °C in the inert gas (nitrogen) atmosphere. When the temperature inside the reactor was stable, oxygen and steam of the temperature of approximately 100 °C were introduced into the reactor. In the second system, after the reactor was heated up to 700 °C, the heating of the reactor was switched off and oxygen and steam were pre-heated to the temperature of 700 °C and fed into the reactor. In the third system a fuel sample in the reactor was heated to the temperature 700 °C and the set temperature was maintained with the resistance furnace. The results showed that sufficient thermal energy required for an effective oxygen/steam gasification process was generated in systems with the external heating of the reactor. The highest hydrogen contents in gas were reported in coal gasification, irrespective of the system configuration. The total hydrogen volume decreased with increasing biomass content in a fuel blend in all studied system configurations. Highlights: Oxygen and steam gasification and co-gasification of coal and sewage sludge. Simulated utilization of an excess High Temperature Reactor (HTR) heat. Sufficient thermal energy provided by the external heating of the reactor.